Tourist product in experience economy - Stasiak, Andrzej (Turyzm/Tourism, 2013)
The turn of the 20th and 21st c. was marked by the development of experience economy, in which the basic commodities are not specific products, but the customers’ emotions, impressions and experiences. Tourism has always been a particular “holiday experience industry”. In recent years, however, the importance of the conscious creation of emotional tourism products has become even greater; we may observe continuous efforts to multiply and intensify tourism experience. The key activities to achieve this goal include transforming tourism infrastructure into unique tourism attractions, enlarging traditional services/service packages by elements providing additional emotions and satisfaction, using modern technologies in order to add virtual entities to real tourism space (augmented reality), as well as to conveniently record tourism experience and share it with the public.